1967
DOI: 10.1128/jvi.1.2.374-383.1967
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Fractions Associated with Semliki Forest Virus Ribonucleic Acid Replication

Abstract: When actinomycin D-treated chick fibroblasts were labeled with 3 H-uridine for varying periods during the log phase of Semliki Forest virus infection, radioactivity was found associated with different cytoplasmic fractions. After a 1-min period of labeling, it appeared in a large cytoplasmic structure which was seen in electron micrographs of infected cells. Sediments of sucrose density gradients of cytoplasmic extracts of these cells also contained these structures. Three forms of vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
58
0

Year Published

1970
1970
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 28 publications
4
58
0
Order By: Relevance
“…Numerous studies have shown that virus-specific RNA polymerase activity is associated with cytoplasmic membranes together with heterogenous RNA (25)(26)(27). The role of 26S RNA as messenger for the structural proteins was finally proven by its in vitro translation in the presence of ER membranes, which yields all structural proteins (28).…”
Section: Replication Of Alphavirus Rnasmentioning
confidence: 99%
“…Numerous studies have shown that virus-specific RNA polymerase activity is associated with cytoplasmic membranes together with heterogenous RNA (25)(26)(27). The role of 26S RNA as messenger for the structural proteins was finally proven by its in vitro translation in the presence of ER membranes, which yields all structural proteins (28).…”
Section: Replication Of Alphavirus Rnasmentioning
confidence: 99%
“…As in other positive-strand RNA viruses, the RCs of alphaviruses are associated with altered intracellular membranes, which were first described in the late 1960s and early 1970s (13,14,18). In these early studies, it was shown that virus replication induces bulb-shaped membrane invaginations with a diameter of ϳ50 nm, which were called spherules.…”
mentioning
confidence: 99%
“…The synthesis of arbovirus-directed ribo nucleic acid has been studied recently in considerable detail with group A viruses. In the case of Semliki forest virus (SFV), three distinct types of RNA were demon strated during viral replication, which were 42S single-stranded, 26S ribonuclease-sensi tive and 20S double-stranded forms [2]. Similar observations have been presented with another group A member, Sindbis virus (SBV) [1].…”
mentioning
confidence: 58%